2010
DOI: 10.1111/j.1468-5957.2010.02185.x
|View full text |Cite
|
Sign up to set email alerts
|

To Trade or Not to Trade: The Strategic Trading of Insiders around News Announcements

Abstract: We argue that insiders' decisions to trade in short windows before news announcements are likely to result from a trade-off between the incentives to capitalize on the foreknowledge of the disclosure and the risk of regulatory scrutiny and reputation loss. We provide evidence that the decision of insiders to buy is driven by this trade-off. We show that insiders strategically choose the amount of shares bought ahead of good news announcements, as they increase their purchases when the price impact of the news … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 42 publications
2
33
1
1
Order By: Relevance
“…Similarly, Baty (2008) found that directors' purchases demonstrated a positive average abnormal return for most of the event window tested. Our results support all these views, and those of Korczak, Korczak and Lasfer (2010) and Lei and Wang (2012) and suggest that directors have the ability to tactically time the market, and that investors who imitate directors' purchases can obtain abnormal returns (Bodie, Kane & Marcus, 2011).…”
Section: Buy Portfoliosupporting
confidence: 77%
“…Similarly, Baty (2008) found that directors' purchases demonstrated a positive average abnormal return for most of the event window tested. Our results support all these views, and those of Korczak, Korczak and Lasfer (2010) and Lei and Wang (2012) and suggest that directors have the ability to tactically time the market, and that investors who imitate directors' purchases can obtain abnormal returns (Bodie, Kane & Marcus, 2011).…”
Section: Buy Portfoliosupporting
confidence: 77%
“…In general, this effect would be expected if sales took place for liquidity reasons. In addition Korczak, Korczak and Lasfer (2010) argue that insider selling before bad news induces regulatory attention and litigation risk, and rational insiders anticipating these risks will be less likely to trade overvalued securities. Given this general insignificance, we drop sales transactions from the subsequent analysis, and concentrate on directors' purchases.…”
mentioning
confidence: 99%
“…The appearance of abnormal returns forerunning announcements is something which has been well documented in the literature (Seyhun 1992, Meulbroek 1992, Jarrell and Poulsen 1989, Dubow and Monteiro 2006, Korczak et al 2010.…”
Section: Discussionmentioning
confidence: 71%
“…This draws a question over the efficacy of the market abuse legislation and its mechanisms for enforcement. Some empirical work suggests that informed trading is curbed when insider trading regulations are introduced, Korczak et al (2010) point to UK evidence supporting this point. Durnev and Nain (2005), who examine a broad sample of twenty one countries, find that on the whole, restrictions on insider activity curb levels of informed trading, but that in companies where the share ownership is concentrated among large shareholders, these restrictions become less effective.…”
Section: What Is the Effect Of Regulation And Enforcement?mentioning
confidence: 99%
See 1 more Smart Citation